Battery Power Control and Monitoring System with Internet of Things Technology - Slamet Winardi; Dwi Suharso, Didik; Purnomo, Hendra; Budijanto, Arief (IJCONSIST JOURNALS, 2021)
Along with the development of battery/ACCU technology, the ACCU charging and loading system has also developed manually or automatically. In this paper, the results of research on the manufacture of tools that function to monitor and control the charging and loading of electrical power will be explained from batteries that are burdened with lights and DC motors through a control panel or android smart phone with IoT technology. This tool is designed to monitor 2 ACCUs, namely ACCU1 and ACCU2. ACCU1 is loaded with lamp and parallel with DC motor load while ACCU2 is loaded with DC motor and parallel with lamp load. If ACCU1 and ACCU2 are full, ACCU1 is loaded with only one lamp and ACCU2 is only loaded with DC motor. For example, ACCU1's electrical power is still within the limits that can be loaded with lights and DC motors while ACCU2 can't be loaded because electric power is not capable of being loaded with DC motors, the DC motor's load will be transferred to ACCU1. So that ACCU1 is loaded with DC lamps and motors and ACCU2 is charging the electricity, as well as for the opposite condition. The design of this tool uses the main component of the ESP32 microcontroller, where this component has been integrated with the wifi module and other supporting circuit modules, namely the current sensor circuit, voltage sensor and OLED display. The software design consists of a program code designer for hardware using C++ and an android smart phone application design using MIT App Inventor. The results of this study are in accordance with the design specifications, namely the device can be used to control charging and loading as well as monitor ACCU1 and ACCU2 electrical power on OLED screens and on Android smart phones screens